Explicit and Implicit Responses of Seeing Own vs. Others’ Emotions: An Electromyographic Study on the Neurophysiological and Cognitive Basis of the Self-Mirroring Technique - Vergallito, Alessandra; Mattavelli, Giulia; Gerfo, Emanuele Lo; Anzani, Stefano; Rovagnati, Viola; Speciale, Maurizio; Vinai, Piergiuseppe; Vinai, Paolo; Vinai, Luisa; Lauro, Leonor J. Romero (Frontiers in Psychology, 2020)
Sensorimotor simulation is described by embodied cognition theories as a human mirror system-based neural mechanism underpinnings emotion recognition. This could have a critical role in Self Mirroring Technique (SMT), a method used in psychotherapy to foster patients’ emotions recognition by showing a video of own face recorded during a moment emotionally salient. However, sensorimotor simulation during own emotion perception has not been investigated so far. In the present study, we measured electromiographic activity from three facial muscles, namely the zygomaticus major (ZM), the corrugator superior (CS) and the levator labii superior (LLS) while participants were presented with videoclips depicting their own face or other unknown faces expressing anger, happiness, sadness, disgust, fear and a neutral emotion. Results showed that processing self vs other expressions differently modulated emotion perception at explicit and implicit sensorimotor level. Participants were significantly less accurate in recognizing self vs others neutral expression and rated fearful, disgusted and neutral expressions as more arousing in self than others condition. Muscle activation resulted congruent with their involvement in emotion expression as reported in literature, confirming the specificity of sensorimotor simulation. EMG data evidenced increased activation of ZM muscle in self compared to others condition only for angry emotion. Activation of CS muscle was reduced for self than others’ expression during processing happy, sad, fearful and neutral expression. Finally, LLS muscle increased activation in self compared to others condition for angry, sad and fearful expressions, whereas reduced activation in self compared to others condition for happy and neutral expressions. Results suggest that with certain types of emotion the sensorimotor simulation is greater for own than others face expression. Such complex pattern of increased and reduced activations for different emotion in self/others expression and the higher arousal response for negative emotions suggest an increased explicit and implicit activation for own negative emotions which might shed light on SMT underlying mechanism.